Investigation of Structure and Chemical Composition of Carbon Nanofibers Developed From Renewable Precursor - Wei, Jiayuan; Geng, Shiyu; Kumar, Manish; Pitkänen, Olli; Hietala, Maiju; Oksman, Kristiina (Frontiers in Materials, 2019)
In this study, lignin-based carbon nanofibers were prepared by electrospinning, followed by carbonization at four different temperatures (800, 1000, 1200, and 1400 °C). The surface and bulk elemental compositions were analyzed by energy-dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy, respectively. In addition, the structure of the prepared carbon nanofibers was characterized by scanning electron microscopy, transmission electron microscopy, focused ion beam microscopy, and Raman spectroscopy. Results showed that all carbon nanofibers, irrespective of the carbonization temperature, had homogeneous structures. They were dense and no phase separation was observed. Moreover, the nanofibers carbonized at 800 °C or 1000 °C predominately contained amorphous carbon and some non-carbon elements. When the carbonization was performed at a higher temperature (1200 °C or 1400 °C), non-carbon elements were effectively removed and nanocrystalline graphite was formed, indicating that high temperature carbonization facilitated the formation of ordered carbon structures.